Observaciones sobre la ecología de los mitílidos de la ría Deseado - Zaixso, Héctor E.; Pastor, Catalina T. (Ecosur, 2025)
The populations of Mytilus edulis chilensis, Aulacomya ater atar, and Brachydontes purpuratus of the ria Deseado (Santa Cruz, Argentina) were studied by transect analysis and objective methods. Progressive application of these methods aüowed to know the population distribution and the composition of the groups of species where mytilids are components. Biocenotic level of some of the groups are reviewed and distnbutions of one of them is widened.